Austrian Solar Brick House 2020 – Energy and Comfort Assessment Report based on a 30 Month Monitoring Period. (June 2016) - Selke, Tim; Perisic, Monika
Abstract: Within the Austrian research project 'Solar Plus Haus' a plus energy building concept for a brick constructed dwelling was developed, planned and put into operation. The building envelope is constructed by using a new generation of energy efficient bricks and the demand for heating, domestic hot water and electricity is covered mainly by energy from solar systems solar, i.e. solar thermal collector and photovoltaics. The future building and its energy system is operating since December 2012. The energy and comfort assessment report of the building operation under real user conditions is documented based on measurement data recorded by a scientific monitoring system. This paper indicates the essential findings from analyzing the measurement data from January 2013 till May 2015. Monthly heat and electricity balances are displayed and selected key performance indicators of the two implemented solar energy systems are calculated. Key findings are drawn and the applied energy building concept is approved by measurements.